Sosialisasi dan Pendampingan Pembuatan Nomor Izin Ber-Usaha Berbasis Resiko untuk Pelaku Usaha di Desa Langlang - Khofifatu Rohmah Adi; Idris; Nurul Ratnawati (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Business Identification Number is an important thing that every business needs to have. The legal basis that regulates that every business must have a permit is government regulation (PP) number 24 of 2018 concerning electronically integrated business licensing services. By having this NIB, many business actors can access it. This access includes access to funding, being able to arrange other permits which can make the product more trusted by consumers. Langlang village is one of the villages in Malang Regency. This village has many business people, but unfortunately the majority of them don't understand about NIB and don't have NIB. The aim of carrying out this service is to educate the public regarding NIB, apart from that the aim of this service is also to provide assistance in managing NIB. The results of this activity are first, business actors have knowledge about the importance of NIB and the benefits of having NIB. Second, after assisting with NIB processing activities, several business actors succeeded in creating NIBs. This activity is felt to be very beneficial for MSMEs.